PELUANG PENGEMBANGAN ECOPRENEURSHIP MENGGUNAKAN PERSPEKTIF KREATIFITAS LAYANAN - Muhammad Yasser Iqbal Daulay; Fachri Eka Saputra; Sularsih Anggarawati (Management Insight: Jurnal Ilmiah Manajemen, 2020)
Ecotourism offers a different form of travel than mass tourism. Ecotourism also provides a learning process to protect and care for nature, and improve the welfare of local communities around or within the ecotourism destination. This study was conducted to find the right approach to developing ecotourism. The main focus is given to the potential of regional ecotourism, including human, cultural, and supporting resources. Research is also conducted to determine the perspective of tourists because meeting their needs cannot be sustainably separated from business goals. This study uses data sources grouped into two, namely primary and secondary data. Primary data obtained through several instruments such as surveys, interviews, and observations.Keywords: Social innovation, ecological tourism, entrepreneurial innovation,